Implementation of Problem-Solving Learning Model in Improving Learning Outcomes at Islamic Education : A Classroom Action Research - Sutiono; Ifham Choli; Mu’allimah Rodhiyana (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
In general, students' perceptions of Islamic religious education subjects tend to be negative. So far, students consider Islamic religious education as the least favorite subject. This type of research is descriptive. (Classroom Action Research, Problem Solving Model with two cycles) Descriptive research describes or answers problems of phenomena or events that occur today, both about phenomena in single variables and correlations and/or comparisons in various variables. Based on the implementation and results of the study, students' learning activities in the Islamic Religious Education (PAI) learning process using the problem solving model (Cycle I) showed that out of 30 students, in terms of the readiness of the Islamic Religious Education learning process, 7 students (23.3%) were classified as strong, 12 students (40%) were classified as moderate, and 11 students (36.6%) were classified as weak. In terms of concentration during the Islamic Religious Education learning process, 11 students (36.6%) were classified as strong, 10 students (33.3%) were classified as moderate, and 9 students (30%) were classified as weak. In terms of motivation during the Islamic Religious Education learning process, 5 students (16.6%) were classified as strong, 14 students (46.6%) were classified as moderate, and 11 students (36.6%) were classified as weak. Meanwhile, in terms of learning achievement measured by grades or report cards, the average score of Islamic Religious Education was 61.3. In terms of motivation during the Islamic Religious Education learning process, 8 students (26.6%) were classified as strong, 9 students (30%) were classified as moderate, and 13 students (43.3%) were classified as weak. Meanwhile, in terms of achievement measured by grades or numbers, the average score of Islamic Religious Education was 80. Thus, the researcher found that there was a significant achievement so that the application of the problem-solving method was considered successful.